Redescriptions of Homoplectra japonica (Banks 1906) and H. albomarginata (Ulmer 1907) (Trichoptera, Hydropsychidae), with descriptions of five new similar species from Japan - Nozaki, Takao (Zootaxa, 2025)
The two known Japanese species of the genus Homoplectra, H. japonica (Banks 1906) and H. albomarginata (Ulmer 1907), are redescribed, and five new similar species are described, H. flagelliformis sp. nov., H. shikoku sp. nov., H. bicornis sp. nov., H. kimi sp. nov., and H. inazui sp. nov. A lectotype is selected for Arctopsyche japonica Banks 1906 for nomenclatural stability. The adults of these species have distinct yellow and black markings on their wings, which are unique among known congeners. A diagnostic species group, the Homoplectra japonica Species Group, is recognized based on wing markings and venation and the shape of the male phallic apparatus. Descriptions are provided for males and females of all species, and the immature stages of H. japonica and H. albomarginata. Larvae of H. japonica and H. albomarginata were found in seeps and small flows in mountain areas.